Effect of foliar spray of growth regulators under organic and chemical fertilizers applied condition on fatty acid composition of safflower: foliar spray of growth regulators and fertilizers on safflower oil quality - Janmohammadi, Mohsen; Sabaghnia, Naser; Nouraein, Mojtaba; Dashti , Shahyar (Journal of Agricultural Sciences (Belgrade), 2022)
In current study we evaluated the impacts of organic and chemical fertilizer as well as growth regulator foliar application on quantitative traits and seed oil content of safflower grown in northwestern Iran. The experiment was done as split-plot (3 ×5) and the main plot was assigned to different fertilizers including organic fertilizer (FYM: farmyard manure 20 t ha-1), full chemical fertilizer (FCF) and no fertilization “control” (NF). The sub-plots were allocated to foliar spray treatments which included control (no-spray application; S0), choline (S1), chitosan (S2) and salicylic acid (S3). The results showed that the application of fertilizer significantly affected the oil and protein content of the seed. However, the effect of FYM was more prominent than FCF on oil qualitative components. A positive significant correlation observed between oil content, protein content, and some fatty acid composition such as oleic acid, arachidonic acid, stearic acid, palmitic acid. The highest values of the previously mentioned traits were obtained by using of FYMS1, FCFS1 and FYMS3. This trend was also clearly obvious for the content of linoleic acid as the main fatty acid in safflower oil. Among the foliar spraying treatments, the most improving effect was obtained with the use of choline. Concluding, improving soil conditions through the application of FYM and appropriate amounts of chemical fertilizers is one of the most important agronomic management to improve the oil quality of safflower seed.